Hermite–Hadamard-Type Integral Inequalities for Functions Whose First Derivatives are Convex - Qi, Feng; Xi, Bo-Yan; Zhang, Tian-Yu (Ukrains’kyi Matematychnyi Zhurnal, 2015)
We establish some new Hermite–Hadamard-type inequalities for functions whose first derivatives are of convexity and apply these inequalities to construct inequalities for special means.